A study on factors affecting employee engagement in construction industry: a case of Visi Nusajaya Sdn Bhd / Rahiyma Mohd Rapi - Mohd Rapi, Rahiyma (Faculty of Business and Management, 2019)
Due to the challenging economic climate, many organizations deciding to restructure and resize for the survival in the marketplace which resulted organizations constantly seek for different methods to keep their employees engaged. Hence, employee engagement can be defining as employee that physically and emotionally show full commitment towards their job to achieve the goals of organization. Therefore, the purpose of this research is to investigate the factors affecting the employee engagement in construction industry specific at Visi Nusajaya Sdn Bhd. This study used convenience sampling techniques and online questionnaire as an instrument to collect data. The data from 72% out of 150 employees are collected then evaluated by using statistical package for the Social Science (SPSS) version 22 software. The result from Multiple Regression analysis indicates that all the elements in predict employee engagement which is leadership, compensation and organizational culture have positive and significant relationship with employee engagement. Moreover, organizational culture found to be the most influential variables towards employee engagement at Visi Nusajaya Sdn Bhd.